(untitled) (Research, Society and Development, 2022)
The use of products containing natural and sustainable substances has shown a remarkable growth in the pharmaceutical and cosmetic market, such as in the compounding pharmacy. This research aimed to develop, characterize, and evaluate the cutaneous bioengineering of natural and sustainable emulsions, providing a vehicle base for topical preparations. Nine O/W emulsions were developed changing the nonionic self-emulsifying wax (Cetearyl Olivate (and) Sorbitan Olivate, Cetearyl Glucoside (and) Cetearyl Alcohol, Candelilla/Jojoba/Rice Bran Polyglyceryl-3 Esters (and) Glyceryl Stearate (and) Cetearyl Alcohol (and) Sodium Stearoyl Lactylate), with or without the anionic co-emulsifier (Sodium Stearoyl Glutamate). They were characterized through preliminary stability tests, rheology and accelerated physicochemical stability study. Four formulations were approved (FB1, FB2, FB3 and FB5), but only FB1 (Cetearyl Olivate (and) Sorbitan Olivate with Sodium Stearoyl Glutamate) was considered stable, being selected for preservative efficacy evaluation and the cutaneous bioengineering. The hydration and transepidermal water loss (TEWL) of stratum corneum were analyzed comparing with a conventional topical vehicle (Emulsifying Wax NF). The clinical study showed that FB1 improved the skin hydration with no significant changes for TEWL, but demonstrated considered values. The FB1 could be classified as “skin friendly” and represents a promising natural and sustainable vehicle in compounded pharmacy preparations.